Psychological changes during the COVID-19 pandemic and its relationship with bruxism and TMD (Research, Society and Development, 2021)
The coronavirus pandemic caused several changes in the population's life, causing psychological consequences that can influence oral health, especially oral diseases that have psycho-emotional factors as their etiology. Objective: perform a literature review about the influence of the COVID-19 pandemic on psychological aspects and its relationship with bruxism and Temporomandibular Disorder (TMD). Methodology: this is a qualitative bibliographic review in which data collection was carried out on the LILACS, BVS, SciELO and PubMed platforms using the descriptors: COVID-19, Oral Health, Psychology, Anxiety, Depression, Bruxism, Temporomandibular Disorders, in English and Portuguese, including articles that addressed the association between psychosocial aspects related to the pandemic by COVID-19 and its connection with bruxism and TMD, in addition to articles that correlated TMD and psychological aspects or that dealt with the pandemic by COVID-19 and its connection with psychological aspects. Results: 19 articles were selected and these showed a relationship between stress, anxiety and depression with bruxism and TMD, with women being the most affected. Conclusion: the COVID-19 pandemic increased levels of stress, anxiety and depression, as well as the incidence and severity of painful symptoms of bruxism and TMD.